Acute on Chronic Liver Failure and Immune Dysfunction: A Mimic of Sepsis - Hensley, Matthew K.; Deng, Jane C. (Seminars in Respiratory and Critical Care Medicine, 2018)
Both the adaptive and innate arms of immunity are altered in patients with cirrhosis, which have both prognostic and clinical implications. Acute on chronic liver failure (ACLF), defined as decompensated cirrhosis with associated organ failure, carries a high risk of 28-day mortality and is marked by a significant inflammatory response. Patients with decompensated chronic liver disease display a shift from a chronic low-grade inflammatory state to one of intense inflammation, followed by the development of immunoparalysis. Considerable heterogeneity exists depending on the nature of the inciting cause and duration of ACLF. In this review, we will highlight the changes that immune cell populations in the liver undergo during decompensated liver disease, underscoring the immunological paradox between inflammation and increased susceptibility to infection that occurs during ACLF and progressive cirrhosis, as well as provide future perspectives regarding potentially useful biomarkers and possible avenues for treatment.
Keywords: acute on chronic liver failure; innate immunity; adaptive immunity; pattern recognition receptors; cytokines; biomarkers